The Level of Soft Skills of Postgraduate Students from Their Viewpoint (A Field Study at Latakia University) : A Field Study at Latakia University (Journal of Hama University, 2026)
The research aims to determine the level of soft skills required for the labor market of a sample of postgraduate students at the Faculty of Education at Latakia University from their viewpoint, in light of the two variables: academic degree and scientific department.To achieve the research objectives, a descriptive approach was used, and a questionnaire was prepared and distributed to a simple random sample of (135) male and female students. The data was collected and statistically analyzed, and the researcher arrived at the following results:- The level of soft skills required for the labor market of postgraduate students is generally average from their viewpoint.- Doctoral students outperform master’s students in the level of soft skills required for the labor market.- The scientific department does not affect the level of soft skills required for the labor market of postgraduate students.In light of the research results, the researcher presented some suggestions, such as: developing integrated educational programs that integrate learning soft skills with academic content to enhance the application of these skills in the context of study and research, and cooperating with professional institutions and the local community to provide training and educational opportunities that allow the practice of soft skills in a practical environment.
Keywords: Level, Soft Skills, Postgraduate Students